2012
DOI: 10.4172/2167-0420.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Related Factors of Female Genital Mutilation (FGM) in Ravansar (Iran)

Abstract: This study was performed to determine the prevalence and related factors of Female Genital Mutilation (FGM) in women visited at the health centers of the city of Ravansar In Kermanshah province, Iran. This cross-sectional study was conducted on 348 women who were visited at 5 health centers of the city of Ravansar. Data was collected using a structured questionnaire and women were examined about exist FGM. The prevalence of FGM was 55.7% among Ravansars' women. It increases with age and about 54.4% were circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 13 publications
11
48
1
Order By: Relevance
“…Mohammed et al [23] also reported that among Egyptian women, tradition, cleanliness, and virginity were the most common motives for FGM/C continuation (100%), followed by men's desire, esthetic factors, marriage, and religion factors (45.2–100%). Our finding is consistent with a previous survey in Iran which showed that FGM/C is a social practice rather than a religious obligation [14]. Generally, there is no reason for FGM/C in Islam.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Mohammed et al [23] also reported that among Egyptian women, tradition, cleanliness, and virginity were the most common motives for FGM/C continuation (100%), followed by men's desire, esthetic factors, marriage, and religion factors (45.2–100%). Our finding is consistent with a previous survey in Iran which showed that FGM/C is a social practice rather than a religious obligation [14]. Generally, there is no reason for FGM/C in Islam.…”
Section: Discussionsupporting
confidence: 92%
“…Tag‐Eldin et al [20] also showed that FGM/C among Egyptian women are mostly performed by local circumcisers who do not use local anesthesia. The data of the present study demonstrate that lower educational level is significantly associated with increased prevalence of FGM/C, which is consistent with previous reports from Iran and African countries [14,17,21–23]. The interesting finding of this study was that the FGM/C in southern rural areas of Iran was associated with Sunni Islam as religion.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations